Impact of Flow Variation on Hydropower Projects in Budhigandaki River Basin of Nepal - Marahatta, Suresh; Devkota, Laxmi Prasad; Aryal, Deepak (Journal of Institute of Science and Technology, 2021)
Daily flow data from 1964 to 2015 of Budhigandaki River at Arughat were analyzed to assess the impact of flow variation at different time scales to the run of the river (RoR) type of hydropower projects. The data show very high inter-annual variation in daily, monthly and seasonal flows. The long term annual average flow at Arughat was 160 m3/s and varies from 120 to 210 m3/s. The long-term averages of loss in flow for both dry and wet seasons based on daily flows for three design discharges (Q90, Q60 and Q40) were found to be respectively -0.72, -1.76 and -1.54 m3/s for dry season and 0.0, -0.27 and -2.26 m3/s for wet season. Although long-term average loss is small, uncertainty increases with the increase in design discharge. The long-term dry season power loss is about 3 % for the RoR projects of the basin however, its annual variation is large. There is a probability of losing the quantum of energy generation by nearly 40% in some years and gaining by about 30 % in some other years in dry season. The impact of flow variation on power production was negative in both dry and wet seasons for RoR projects of Budhigandaki basin. This study concludes that uncertainty arising from daily flow variation should be assessed while estimating energy generation in hydropower projects. Intra-annual flow variation is, thus, to be taken into consideration while calculating the power generated by the RoR plants; and it should be reflected in power purchase agreement.